A Semiotic Analysis on Robert Frost’s Poem Love and a Question Based on Charles Sander Peirce’s Triangle Theory - Anita Candra Dewi; Asrifan, Andi (International Journal of Sustainable Applied Sciences, 2023)
This research aims to identify Robert Frost's symbols in "Love and a Question" and disclose their meanings using Peirce's triangle theory. This study uses descriptive and qualitative methods to examine Robert Frost's Love and a Question's symbols. Interpreting poem symbols is the focus of this research. This library research uses books and scientific materials to ensure objectivity. Finally, using semiotics and Peirce's triangle, the researcher explains Robert Frost's poem Love and a Question's symbols. The poem Love and a Question's symbolic words' significance through Peirce's triangle theory. The symbolic terms were: green-white stick signified lengthy journey, stranger symbolized uncertainty, rich a curse symbolized precious, and sky symbolized unpredictable future. The poem's represented words all have a life-related significance. The actual meaning of life is building a household as a newlywed couple. Also included is a purpose of life that is no longer defined by wealth because greediness can lead to suffering.